Analysis and simulation of vector controlled bearingless induction motors - Ungku Amirulddin, Ungku Anisa (2006)
The concept of bearingless motors, which combine both motoring and rotor bearing capabilities, is appealing especially in high speed and high power machine applications. Although extensive research has been carried out on permanent magnet and reluctance types of bearingless motors, studies on the induction motor type are less successful. This thesis addresses the bearingless induction motor based on the concept of dual-pole windings, one controlling the motor torque and the other the generated radial forces. A modelling approach is undertaken to investigate the effect of induction machine design on radial force generation and motor levitation under both steady state and transient conditions. The simulation is based on the dynamic reluctance mesh model embedded in vector control systems for the decoupled control of torque, flux and radial force. This is achieved through modification of a previously developed computer software for modelling induction motors in order to model the control of bearingless induction motors.